2023
DOI: 10.1002/biof.1958
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the ubiquitin‐proteasome system by phytochemicals: Therapeutic implications in malignancies with an emphasis on brain tumors

Abstract: Regarding the multimechanistic nature of cancers, current chemo‐ or radiotherapies often fail to eradicate disease pathology, and frequent relapses or resistance to therapies occur. Brain malignancies, particularly glioblastomas, are difficult‐to‐treat cancers due to their highly malignant and multidimensional biology. Unfortunately, patients suffering from malignant tumors often experience poor prognoses and short survival periods. Thus far, significant efforts have been conducted to discover novel and more e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 444 publications
(704 reference statements)
0
1
0
Order By: Relevance
“…The decrease in AP-1 activity may result in decreased invasion since this TF induces the expression of MMPs. A reduction in NF-κB may be a consequence of decreased PKB/Akt phosphorylation [15]-resulting in decreased NF-κB activation by Akt-and decreased proteasome degradation of the NF-kB inhibitor IκB [54], induced by curcumin. Decreased NF-κB activity-which is upregulated in glioma-induced by curcumin may result in decreased proliferation, cell survival, angiogenesis, inflammation, and increased apoptosis since this TF directly regulates the expression of genes involved in these processes [55].…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in AP-1 activity may result in decreased invasion since this TF induces the expression of MMPs. A reduction in NF-κB may be a consequence of decreased PKB/Akt phosphorylation [15]-resulting in decreased NF-κB activation by Akt-and decreased proteasome degradation of the NF-kB inhibitor IκB [54], induced by curcumin. Decreased NF-κB activity-which is upregulated in glioma-induced by curcumin may result in decreased proliferation, cell survival, angiogenesis, inflammation, and increased apoptosis since this TF directly regulates the expression of genes involved in these processes [55].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy medicines, e.g., docetaxel (DTX), irinotecan, 5-fluorouracil (5-FU), cisplatin, and paclitaxel (PTX), are utilized in treating diverse cancers; nevertheless, their efficacies are confined, owing to the emergence of drug resistance, inducing non-selective toxicity and producing significant adverse reactions [5]. It is expected that the efficiency of pharmacological therapy will improve when combined with treatments that use phytochemicals, and the unwanted effects will become less severe as a result [6][7][8]. For instance, the findings showed that curcumin (Cur, an active ingredient from Curcuma longa with multiple biological effects [9][10][11][12][13][14][15][16][17]), in combination with chemotherapeutics, had a wider range of anti-cancer action and a lower risk of severe side effects than standard chemotherapy medications [18,19].…”
Section: Introductionmentioning
confidence: 99%